2019
DOI: 10.3390/w11030497
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Novel Climate Adaptation Algorithm for Climate Risk Assessment

Abstract: To comprehensively assess the climate risk originating from climate change, this study aims at developing a novel climate adaptation algorithm, representing not only on the basis of Climate Change Adaptation Six Steps (CCA6Steps), but also innovations in climate risk template. The climate risk template is proposed as a climate risk analysis tool based on the procedure of CCA6Steps, including the identification of problems and objectives, the analysis of current and future risks, and the assessment of adaptatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 21 publications
0
11
0
1
Order By: Relevance
“…Two different drought risk assessments were performed -one for irrigated agricultural systems and one for rainfed systems -at the municipality level. Following methodological suggestions of the International Standard on Risk Norm ISO/IEC 31010 (IEC (International Electrotechnical Commission), 2019), Frigerio and De Amicis (2016) and Tung et al (2019) the CVI and hazard/exposure for each agricultural system was classified into seven classes using equal intervals from the maximum, and then those classes were combined to obtain the final risk for each agricultural system (Supplementary material Fig. S8).…”
Section: Risk Assessmentmentioning
confidence: 99%
“…Two different drought risk assessments were performed -one for irrigated agricultural systems and one for rainfed systems -at the municipality level. Following methodological suggestions of the International Standard on Risk Norm ISO/IEC 31010 (IEC (International Electrotechnical Commission), 2019), Frigerio and De Amicis (2016) and Tung et al (2019) the CVI and hazard/exposure for each agricultural system was classified into seven classes using equal intervals from the maximum, and then those classes were combined to obtain the final risk for each agricultural system (Supplementary material Fig. S8).…”
Section: Risk Assessmentmentioning
confidence: 99%
“…Previous studies suggest that drought can affect different areas and people within the same area differently [17][18][19][20]. Tung et al [18] revealed that there is an association between climate risk components, including hazard, exposure, and vulnerability. Eckstein et al [19] confirmed that emerging economies are more vulnerable to climate risk compared to developed economies.…”
Section: Introductionmentioning
confidence: 99%
“…Abeygunawardena et al [20] are of the opinion that climatic changes progressively affect the poor and, as such, there is a need for adaptation strategies. The subsequent effects felt by households or individuals, as well as their coping strategies or mechanisms, could be influenced greatly by their previous status in terms of access to various capital or assets, such as wealth, information, financial aid, and loans [17,18]. The problem is that vulnerability is not accounted for, and smallholder farmers are the ones who are affected the most, being the most vulnerable during the occurrence of drought because they depend on agriculture for their livelihood [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pengkajian langkah-langkah strategis yang harus diambil dalam rangka meminimalisir Fascioliasis didasarkan pada hasil olah data risiko suatu wilayah terhadap Fascioliasis sehingga penelitian dilakukan secara komprehensif baik aspek fisik maupun sosial di sentra peternakan di DIY. Penilaian risiko berdasarkan dari penelitian (Tung et al, 2019) Lingkungan yang basah juga dipengaruhi oleh curah hujan dimana curah memberikan gambaran mengenai seberapa sering suatu lahan akan basah. Curah hujan juga merupakan suatu indikator bahwa daerah tersebut memiliki tingkat kebasahan yang mempunyai hubungan dengan tingkat kerawanan daerah tersebut terhadap penyakit parasit cacing hati.…”
Section: Metode Penelitianunclassified